The Mobility Challenge for Growth and Integration in Europe - Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2013)
Open and flexible labor markets foster growth, development and integration in Europe. The single European labor market is still a vision, however, whereas the core challenge is a lack of sufficient mobility. The presentation discusses the value of labor mobility for economic prosperity and its determinants. Labor migration and not welfare migration dominates reality and supports economic equality. It does not depress wages or take jobs away. A brain drain for sending countries does not have to happen. Diaspora economies provide potentials for economic and political collaborations. Europe will face in the future a much higher level of circular and permanent migration.
Keywords: D61; F15; F22; F55; F66; J15; J61; J71; 330; migration; labor mobility; welfare migration; diaspora economics; circular migration